SLC6A1 variant pathogenicity, molecular function and phenotype: a genetic and clinical analysis - Arthur Stefanski; Eduardo Pérez-Palma; Tobias Brünger; Ludovica Montanucci; Cornelius Gati; Chiara Klöckner; Katrine M Johannesen; Kimberly Goodspeed; Marie Macnee; Alexander T Deng; Ángel Aledo-Serrano; Artem Borovikov; et al. (My University, 2023)
Abstract Genetic variants in the SLC6A1 gene can cause a broad phenotypic disease spectrum by altering the protein function. Thus, systematically curated clinically relevant genotype-phenotype associations are needed to understand the disease mechanism and improve therapeutic decision-making. We aggregated genetic and clinical data from 172 individuals with likely pathogenic/pathogenic (lp/p) SLC6A1 variants and functional data for 184 variants (14.1% lp/p). Clinical and functional data were available for a subset of 126 individuals. We explored the potential associations of variant positions on the GAT1 3D structure with variant pathogenicity, altered molecular function and phenotype severity using bioinformatic approaches. The GAT1 transmembrane domains 1, 6 and extracellular loop 4 (EL4) were enriched for patient over population variants. Across functionally tested missense variants (n = 156), the spatial proximity from the ligand was associated with loss-of-function in the GAT1 transporter activity. For variants with complete loss of in vitro GABA uptake, we found a 4.6-fold enrichment in patients having severe disease versus non-severe disease (P = 2.9 × 10−3, 95% confidence interval: 1.5–15.3). In summary, we delineated associations between the 3D structure and variant pathogenicity, variant function and phenotype in SLC6A1-related disorders. This knowledge supports biology-informed variant interpretation and research on GAT1 function. All our data can be interactively explored in the SLC6A1 portal (https://slc6a1-portal.broadinstitute.org/).
Keywords: autism; epilepsy; genetics; neurodevelopmental disorder; slc6a1; gaba plasma membrane transport proteins; genetic association studies; humans; mutation, missense; phenotype; virulence; beta lactamase; gaba transporter 1; 4 aminobutyric acid carrier; slc6a1 protein, human; 4 aminobutyric acid uptake; absence epilepsy; article; atonic seizure; childhood absence epilepsy; cohort analysis; controlled study; crispr-cas9 system; developmental delay; developmental disorder; disease severity; epilepsy; focal epilepsy; gene frequency; generalized epilepsy; genetic variability; genotype; hek293t cell line; human; in vitro study; intellectual impairment; learning disorder; lennox gastaut syndrome; loss of function mutation; major clinical study; mass spectrometry; myoclonus seizure; pathogenicity; phenotype; protein structure; refractory epilepsy; scintillation counting; temporal lobe epilepsy; whole exome sequencing; genetic association study; genetics; metabolism; missense mutation; phenotype; virulence